2019
DOI: 10.21608/pssjn.2019.68002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pathways of Postoperative Nursing Care for Women Undergoing Gynecological Operations at Port Said Hospitals

Abstract: Background:The aim of the present study is to investigate the effect of clinical pathways of postoperative nursing care for patients undergoing gynecologic operations on the postoperative outcome.Subjects and Methods: the study was conducted at Obstetric and Gynecologic Department. A total of 112 women undergoing gynecological operation (56 study group who received pre and postoperative care of clinical pathway, and 56 control group who received pre and postoperative routine care of the hospital).Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…The current study showed that more than half of studied women had secondary level of education or its equivalent in both groups This finding was in line with Heeba, et al [15] study of "clinical pathway of postoperative nursing care for women undergoing gynaecological operation at port said hospitals" found that more than half from studied women had secondary level of education in both groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study showed that more than half of studied women had secondary level of education or its equivalent in both groups This finding was in line with Heeba, et al [15] study of "clinical pathway of postoperative nursing care for women undergoing gynaecological operation at port said hospitals" found that more than half from studied women had secondary level of education in both groups.…”
Section: Discussionsupporting
confidence: 91%
“…It included 10 questions as wound infection, pneumothorax, vaginal bleeding ……etc. (used for study group and control) Ali, et al [3] and Heeba, et al [15].…”
Section: Tools For Data Collection 131 Tools Of Data Collection Tomentioning
confidence: 99%
“…Following postpartum standardized care guidelines, which might be administered by a maternity nurse after caesarean section surgery, could enhance postoperative outcomes significantly. These include a faster recovery of gastrointestinal function, better pain relief with less opiate prescriptions, a shorter hospital stay, and high woman satisfaction with significant cost savings while reducing level complication and readmission rates (Aljabri et al, 2020).. Few studies have examined at postpartum standardized care guidelines in women who have had caesarean sections, and the majority of cohorts were small and only included women who experienced postpartum problems (Heeba, Nasr & Ali Abou Elsadat, 2019). In the meantime, no research has been done on this topic at the Alazher university hospital in Damietta.…”
Section: Significance Of Studymentioning
confidence: 99%
“…An increasing body of evidence, including randomized controlled studies Adamina et al (2011), has shown that following postpartum care guidelines speeds recovery and saves morbidity and expense while maintaining women's satisfaction and quality of life. Few studies have assessed postpartum care guidelines in caesarean section surgery, and the majority of cohorts were small and only included women who had postpartum problems (Heeba, Nasr & Ali Abou Elsadat, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Heeba M, conducted a study to investigate the effect of clinical pathways of postoperative nursing care for patients undergoing gynaecologic operations on the postoperative outcome. The study shows that the clinical pathway was effective in improving postoperative outcomes related to early ambulation, early oral intake, bowel mobility, hours to remove catheters and drains, a short length of stay and patient satisfaction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%